Pilot cum scaling: Inclusion of nutrient-dense small fish powder in diets among pre-school children of Anganwadi Centers and LP School children through a partnership approach at Bongaon Block in Kamrup District of Assam, India - Ratha, Baishnaba; Bayan, Baban; Shenoy, Neetha; Panemangalore, Arun (WorldFish, 2024)
This report documents an innovative pilot project aimed at combating malnutrition among children. The initiative introduced small fish powder—a rich source of essential micronutrients—into the diets of pre-school children at Anganwadi Centers and primary school children, leveraging a collaborative approach with local government departments, Anganwadi workers, school authorities, and self-help groups. The report highlights the project's design, implementation, and scaling strategy, emphasizing its success in improving dietary diversity and nutritional outcomes while fostering community engagement and capacity building to ensure sustainability.